Social Fear of Crime and Its Consequences - Leszek Wilk; Bogdan Fibinger (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2020)
Social fear of crime is a phenomenon of interest to scientific disciplines. The present study draws primarily on the achievements of criminology. It shows that there are different ways of interpreting fear of crime, explaining its causes and responding to it. The conclusions also depend on the perspectives - whether it is the perspective of an individual, small social groups or large social structures. There are always objective and subjective elements in evaluations, including irrational ones. The latter hinder rational criminal policy. Fear of crime has negative social consequences, such as a loss of citizens' sense of security, aggressive attitudes, a loss of trust in law enforcement services, a reduction in the need for social contact, a reduction in the willingness to provide assistance - as a result, an increase in crime and an even greater sense of threat, particularly affecting socially weaker groups. The rigour and emotional approach to the problem of punishing criminals, resulting from the fear of crime, gives rise to the phenomenon of so-called penal populism, often used by politicians with the participation of the media. Finally, the economic costs of social fear of crime are not insignificant. For these reasons, the phenomenon should not be underestimated, but should not be overestimated, because in the context of other threatening situations and various dangers, it does not constitute the main feeling of threat to citizens and is far behind such fears as social, economic, health, fear of war, etc. Favourable developments in areas other than internal security, e.g. increased prosperity reduces social fear of crime more than restrictive criminal law.